Innate Lymphoid Cells - Neglected Players in Multiple Sclerosis - Sadeghi Hassanabadi, Negar; Broux, Bieke; Marinović, Sonja; Gotthardt, Dagmar (Frontiers in Immunology, 2022)
Multiple sclerosis (MS) is a highly debilitating autoimmune disease affecting millions of individuals worldwide. Although classically viewed as T-cell mediated disease, the role of innate lymphoid cells (ILC) such as natural killer (NK) cells and ILC 1-3s has become a focal point as several findings implicate them in the disease pathology. The role of ILCs in MS is still not completely understood as controversial findings have been reported assigning them either a protective or disease-accelerating role. Recent findings in experimental autoimmune encephalomyelitis (EAE) suggest that ILCs infiltrate the central nervous system (CNS), mediate inflammation, and have a disease exacerbating role by influencing the recruitment of autoreactive T-cells. Elucidating the detailed role of ILCs and altered signaling pathways in MS is essential for a more complete picture of the disease pathology and novel therapeutic targets. We here review the current knowledge about ILCs in the development and progression of MS and preclinical models of MS and discuss their potential for therapeutic applications.